Medicine and the Task of Healing - Paul A. Komesaroff (Kerman University of Medical Sciences, 2013)
To understand the traditional description of medicine as a practice of healing, it is necessary to examine its relationships with both science and ethics. The "scientific" component of medicine includes an acknowledgment of the influence of social, cultural and environmental factors on the functioning of the organism. The "ethical" component is often presented as merely supplementary but actually provides the conditions of possibility of knowledge. "Healing" then appears as what joins the two together: the site where science is applied in the service of ethics and where ethics encounters science. This perspective allows us to reconsider medicine as a project to healing complex wounds that manifest themselves at the physical, psychological, emotional and cultural levels.